Estimasi Emisi CO2 Pada Pekerjaan Perakitan Baja Tulangan dengan Ruang Lingkup Gate To Install - Arvin Philander Cahyono; Liem Kresna Mulia; - Hermawan; Endro Giyanto (Universitas Katolik Soegijapranata Semarang, 2019)
Reinforcing steel is one of the major construction materials which produces significant CO2 emission. In addition, reinforcing steel is also the main material in various construction Project type. Type of construction project which uses large amounts of reinforcing steel is high-rise buildings. The growth of high-rise buildings almost all over the world tend to increase. The tendency can be shown in Indonesia which has a total of 621 high-rise buildings. With this amount, Indonesia is one of 10 countries which have a significant tendency in the growth of high-rise buildings. Furthermore, the large and small of CO2 emission of reinforcing steel is indicated sourced from the supply chain as well. Hereafter, the reinforcing steel on the site needs some heavy equipment such as bar bending, bar cutter and transportation using tower cranes. The contribution of CO2 emission from the supply chain and install on site becomes important as it contributes in shaping cycles within the construction project. The existence of such cycles can be shown by the source and the amount of CO2 emission produced by each step. By using LCA, the source and amount of CO2 emission from each step can be found. The scope developed in this research is cradle to install. The result of the research shows that the size of CO2 emission in the cradle section range from 99 kg.CO2/m3-171 kg.CO2/m3. Furthermore, the size of CO2 emission in the supply chain section ranges from 10 kg.CO2 / m3-21 kg.CO2/m3. The size of CO2 emission ranges between 1 kg.CO2/m3-5 kg.CO2/m3. The result of the research is that reinforcing steel cradle is the biggest source of CO2 emission. The CO2 emission on the site is the smallest compared to the cradle and supply chain, but they cannot be ignored because they also contribute to and make a big determinant of CO2 emission in the construction project.